Prediction of Diabetes by Measuring the Cross-Sectional Area of Median and Tibial Nerves. Is It a Good Predictor? - Iqbal, Yusra; Farooq, Syed Muhammad Yousaf; Malik, Sajid Shaheen; Kinza Rasool; Gilani, Syed Amir; Mahnoor Wahid; Attia Safdar; Arwa Riaz (Jordan Medical Journal, 2025)
Objective: To evaluate the sonography of median and tibial nerve in diabetic and non-diabetic individuals. Method: In this Case-Control study 90 individuals divided into 45 diabetics and 45 non-diabetics were examined. The study was performed at Sehat Medical Complex Hanjarwal Lahore. Independent sample T test was used to compare it between two groups. Result: There were 90 individuals recruited during our study. There were 52(57.8%) females and 38(42.2%) males. The average age of individuals was 42.17 ±14.75. The average size of the median nerve in diabetic patients was 12.1 ±2.1 mm2 and in non-diabetics was 6.88 ±1.3mm2.The average size of the tibial nerve in diabetic patients was 15.06 ± 3.0mm2 and in non-diabetics was 8.3 ±2.4mm2. There was a significant difference p˂0.005. For the tibial nerve, females (Mean = 12.0 ± 4.2 mm) exhibit a slightly larger size compared to males (Mean = 11.2 ± 4.5 mm). In terms of the Median Nerve, males have a mean size of 9.44 ± 2.8 mm, while females have a slightly larger mean of 9.6 ± 3.4 mm. Conclusion: According to our research, the vast majority of diabetic patients who underwent ultrasonography had a significant increase in the cross-sectional area of nerves in diabetic patients as compared to healthy control individuals. Moreover, these results suggest that sonographic examinations are useful for the early diagnosis of diabetic neuropathy.